2024
DOI: 10.1186/s13148-024-01650-w
|View full text |Cite
|
Sign up to set email alerts
|

Novel histone post-translational modifications in Alzheimer’s disease: current advances and implications

Yuanyuan Qin,
Ping Yang,
Wanhong He
et al.

Abstract: Alzheimer’s disease (AD) has a complex pathogenesis, and multiple studies have indicated that histone post-translational modifications, especially acetylation, play a significant role in it. With the development of mass spectrometry and proteomics, an increasing number of novel HPTMs, including lactoylation, crotonylation, β-hydroxybutyrylation, 2-hydroxyisobutyrylation, succinylation, and malonylation, have been identified. These novel HPTMs closely link substance metabolism to gene regulation, and an increas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2025
2025

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 86 publications
0
1
0
Order By: Relevance
“…Nonetheless, other DNA and RNA modifications not described in this review have been shown to or have the potential to influence AD pathology. Other reviews have explored the roles of histone modifications in AD and other neurological disorders, such as Park et al (2022) , Santana et al (2023) , and Qin et al (2024) .…”
Section: Introductionmentioning
confidence: 99%
“…Nonetheless, other DNA and RNA modifications not described in this review have been shown to or have the potential to influence AD pathology. Other reviews have explored the roles of histone modifications in AD and other neurological disorders, such as Park et al (2022) , Santana et al (2023) , and Qin et al (2024) .…”
Section: Introductionmentioning
confidence: 99%